2017
DOI: 10.3389/fpsyg.2017.01594
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Mindsets Concerning the Malleability of Intelligence and the Appraisal of Achievement in the Context of Feedback

Abstract: The pedagogical beliefs (e.g., beliefs or “mindsets” concerning the malleability of intelligence) that teachers hold may have a far-reaching impact on their teaching behavior. In general, two basic mindsets can be distinguished with regard to the malleability of intelligence: fixed (entity) and growth (incremental). In this article, we present two studies investigating the associations between teachers' mindset and (1) their appraisal of students' achievements and (2) the feedback they provide. Study 1 focuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 50 publications
(73 reference statements)
1
38
0
1
Order By: Relevance
“…In particular, teachers should communicate clearly that everybody can learn and improve his or her abilities and that mistakes and questions are welcome in the classroom because they are valuable opportunities to learn. In general, instructional practices and behavioral norms that focus on students' traits and performance are likely to support fixed mindsets, whereas practices and norms that focus on learning processes and development are likely to support growth mindsets (see also [41]). It can thus be assumed that instructional practices and classroom norms influence whether growth mindsets are established in the classroom after a training or not.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, teachers should communicate clearly that everybody can learn and improve his or her abilities and that mistakes and questions are welcome in the classroom because they are valuable opportunities to learn. In general, instructional practices and behavioral norms that focus on students' traits and performance are likely to support fixed mindsets, whereas practices and norms that focus on learning processes and development are likely to support growth mindsets (see also [41]). It can thus be assumed that instructional practices and classroom norms influence whether growth mindsets are established in the classroom after a training or not.…”
Section: Introductionmentioning
confidence: 99%
“…To be able to use STEAM to measure more stable variables, such as the mindset beliefs that students or teachers have, researchers are encouraged to additionally assess construct validity before implementing the coding scheme (Suen, 2010). That being said, individuals' beliefs about the nature of abilities do not always correspond to their behavior (De Kraker-Pauw et al, 2017). Indeed, mindset-related actions are inherently contextualized in the immediate interaction, and in the case of adults, driven by theories regarding how best to motivate children (Haimovitz & Dweck, 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Teachers who communicate growth messages in class emphasize that intelligence and other characteristics are malleable (Boaler, 2013 ; de Kraker-Pauw et al, 2017 ; Sun, 2015 ). This can be communicated in diverse ways, but research has focused predominantly on how teachers provide feedback to their students, including praise or criticism.…”
Section: Overview Of the Literature: Communication Of Growth And Fixementioning
confidence: 99%
See 1 more Smart Citation
“…This is a legitimate perspective, but we cannot exclude that there may still be a difference between explicitly formulated opinions, as in our interviews, and more implicit beliefs driving actual behavior. For example, a recent study showed that the self‐reported growth mindset of teachers was not reflected in their teaching behavior, that is, it was not associated with providing more growth‐oriented feedback to students (de Kraker‐Pauw, Van Wesel, Krabbendam, & Van Atteveldt, ). In other words, although stakeholders may explicitly acknowledge the importance of individual differences, they may still behave differently.…”
Section: Discussionmentioning
confidence: 99%